Bridging the Shakespearean and Jataka Narratives: A Narratological Analysis of Othello and Sambulā Jātaka (519) - Dilani, Nipunika (Religions, 2024)
This study explores the thematic and structural parallels between William Shakespeare’s Othello and the Sambulā Jātaka (519) from ancient Buddhist literature. Through a detailed narratological analysis, this study examines the narrative structure, narrator and narrative perspectives, focalization, temporal aspects, and narrative techniques employed in both texts. By investigating how each narrative addresses themes of sexual jealousy, trust, and human frailty, this paper highlights the universal nature of these emotions and their impact across two cultural contexts. This study employs the qualitative approach of research analyzing the texts, Othello and the Sambulā Jātaka, as a sample representing two larger canons. The analysis reveals that both genres utilize the narratological aspects to reveal the destructive nature of most of the above underlying emotions, bringing them to the surface and creating a powerful resonance that transcends time and geography. This comparative study underscores the timeless relevance of these narratives and their shared exploration of the complexities of human relationships and the destructive power of irrational suspicions.